2014
DOI: 10.1149/2.013405jes
|View full text |Cite
|
Sign up to set email alerts
|

Ta-Doped Li7La3Zr2O12for Water-Stable Lithium Electrode of Lithium-Air Batteries

Abstract: Garnet-type high lithium ion conductivity solid electrolytes with nominal compositions of Li 7-x La 3 Zr 2-x Ta x O 12 (x = 0-0.7) were prepared by using a sol-gel precursor and are proposed as the protective layer for a water-stable lithium electrode for lithium-air rechargeable batteries. The Li 6.75 La 3 Zr 1.75 Ta 0.25 O 12 (LLZ-0.25Ta) composition sintered at 1,180 • C for 36 h showed the highest relative density of 96.7% and resistance to water permeation. The LLZ-0.25Ta was stable in contacting with lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 38 publications
(69 reference statements)
6
99
1
Order By: Relevance
“…They concluded that Li 6 La 3 Zr 2 O 11.5 was stable in saturated LiCl with respect to the structure and electrical conductivity, but unstable in water and acidic and alkaline solutions. Yamamoto et al [ 62 ] synthesized Li 7-x La 3 Zr 2-x Ta x O 12 ( x = 0-0.7) with various Ta contents and found Li 6.75 La 3 Zr 1. 75 Ta 0.…”
Section: Chemical Stabilitymentioning
confidence: 99%
“…They concluded that Li 6 La 3 Zr 2 O 11.5 was stable in saturated LiCl with respect to the structure and electrical conductivity, but unstable in water and acidic and alkaline solutions. Yamamoto et al [ 62 ] synthesized Li 7-x La 3 Zr 2-x Ta x O 12 ( x = 0-0.7) with various Ta contents and found Li 6.75 La 3 Zr 1. 75 Ta 0.…”
Section: Chemical Stabilitymentioning
confidence: 99%
“…The reversible phase transition between the tetragonal and H.T.-cubic phases proceeds very fast at 650°C; therefore, the H.T.-cubic phase with stoichiometric composition cannot be quenched at room temperature [14]. It has been considered that the H.T.-cubic LLZ with the lithium-disordered structure could be stabilized at room temperature by the replacement of Li + for Al 3+ , which originated as contamination from the aluminum crucible used during the high temperature sintering period [14,17,18]. The H.T.-cubic phase was successfully stabilized at room temperature by the addition of Al 2 O 3 sources and Rangasamy et al suggested that at least 0.204 mol of Al 3+ is required to obtain the H.T.-cubic phase of Li 7 − 3x Al x La 3 Zr 2 O 12 at room temperature [16].…”
Section: Introductionmentioning
confidence: 99%
“…Lithium dendrite formation has been reported for Nb-doped, 58 Ta-doped 59 and Al-doped 60 ¹2 and the diameter of these black circles was increased by the further polarization. The black circles may be due to the lithium dendrite growth at the grain boundary.…”
Section: Lithium Dendrite Formation With Solid Electrolytesmentioning
confidence: 92%